Functional features of the heart in cyclists - Medvedev, I. N.; Razzhivin, O. A.; Dorontsev, A. V.; Belyaev, V. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effect of training loads on the functional parameters of the heart of cyclists.